Social Perception of Living Walls in Quito: A Study of Four Vertical Gardens. Issue 1 (May 2020) - Maron, A; Ramirez, F
Abstract: As part of a transdisciplinary study on the benefits of vertical gardens in Quito (Ecuador), social research was carried out to determine people's perceptions and level of understanding of living walls. The four gardens studied were on the campus of the Pontifical Catholic University of Ecuador (semi-public), in the San Blas Plaza (public), in the Governmental Financial Platform (semi-public), and in the private offices of an architecture firm (private). The research was organized into two primary phases; the first involved carrying out observations of each of the four vertical gardens. The observations led to the characterization of the immediate surroundings of the gardens, an understanding of accessibility (particularly for people with disabilities and security-related limitations), as well as of the number of people who passed through the space and the type of interactions they had with the garden. During the second phase, a total of 57 interviews were carried out with people in the areas surrounding each of the vertical gardens. The interviews identified basic demographic information about the respondents, how they define vertical gardens, the type, and frequency of their interactions with the specific garden of study, and their perceptions of the benefits and drawbacks of vertical gardens. The information from the interviews was processed to identify key trends related to each garden, as well as identify trends across the four gardens. The results revealed varying levels of understanding of vertical gardens, the influence of esthetics on people's perceptions, and finally ideas around the benefits and drawbacks of vertical gardens. The conclusions demonstrated a gap between social perceptions of vertical gardens, particularly in public spaces, and the gardens' potential ecological and air quality contributions to the city.